Potensi Penggunaan Ekstrak Daun Kayu Manis (Cinnamomum Burmannii) Sebagai Antibiotik Alternatif Berbasis Herbal - Satrya Jati Jayachrisna (Yayasan Pendidikan Medika Indonesia, 2025)
Infections caused by bacteria continue to pose a significant public health challenge, especially in developing nations. The excessive and improper use of synthetic antibiotics has greatly contributed to the rise of antibiotic-resistant bacteria, which is currently responsible for around 1.27 million deaths each year. This situation highlights the urgent need for safer and more sustainable alternative therapies, including the use of plant-based antimicrobials. One promising option is the leaf of Cinnamomum burmannii, which is packed with various bioactive compounds like flavonoids, alkaloids, saponins, tannins, and phenols. These compounds demonstrate multiple antibacterial mechanisms, such as disrupting bacterial cell membranes, inhibiting the synthesis of nucleic acids and proteins, inactivating enzymes, and interfering with energy metabolism. Several in vitro studies have demonstrated that extracts of Cinnamomum burmannii leaves possess moderate to strong antibacterial activity against pathogens such as Staphylococcus aureus, Escherichia coli, and Salmonella Typhi. Besides its efficacy, the use of Cinnamomum burmannii leaf extract is considered safer, more economical, and less likely to induce resistance. However, the application of this extract in clinical settings remains limited due to the lack of in vivo and clinical studies addressing its safety, toxicity, pharmacokinetics, and pharmacodynamics. Additional research is essential to fully investigate the therapeutic potential of Cinnamomum burmannii leaf extract as an evidence-based alternative antibacterial agent.